Application of Maggot Used Organic Fertilizer (Kasgot) in Food Crops and Horticulture Cultivation - Purwanto; Nurchasanah, Siti; Naila Khusna Syarifah, Risqa; Na'imatul Bayyinah, Lafi; Hanifa, Hana; Rahayuaningsih Ratnaningsih, Hanim (Prospect Publishing, 2024)
This community service was aimed to socialize and apply maggot frass as organic fertilizer in the cultivation of food crops and horticulture in the